Pengembangan Sistem Manajemen Waktu Berbasis Mobile dengan Pendekatan Teknik Pomodoro - Pratama, Faras Sulthan; Widodo, Tri (TIN: Terapan Informatika Nusantara, 2025)
Time management poses a critical challenge for the academic community, particularly students, in the era of digital transformation. Distractions arising from excessive device usage often compromise concentration and productivity while escalating academic stress. This study aims to develop a mobile-based application implementing the Pomodoro Technique to assist users in managing work and rest intervals in a structured manner. The system development follows the Prototyping approach, encompassing requirements analysis, interface design, system coding, and functional testing. Constructed using the Flutter framework with the Dart programming language, the application utilizes SharedPreferences for a lightweight local data storage mechanism. Black Box testing results demonstrate that key features such as the custom timer, to-do list management, and theme personalization operate according to functional specifications. The implementation of this system proves effective in providing students with a tool to independently enforce time discipline, thereby minimizing potential mental fatigue and enhancing daily productivity.